2022
DOI: 10.1186/s11658-022-00315-x
|View full text |Cite
|
Sign up to set email alerts
|

ERp57/PDIA3: new insight

Abstract: The ERp57/PDIA3 protein is a pleiotropic member of the PDIs family and, although predominantly located in the endoplasmic reticulum (ER), has indeed been found in other cellular compartments, such as the nucleus or the cell membrane. ERp57/PDIA3 is an important research target considering it can be found in various subcellular locations. This protein is involved in many different physiological and pathological processes, and our review describes new data on its functions and summarizes some ligands identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 140 publications
(164 reference statements)
0
33
0
Order By: Relevance
“…Interestingly, we found that several Lhx1os interactors correspond to proteins associated with the ER; among them, calreticulin, calnexin, and PDIA3 are known to transiently bind newly synthesized glycoproteins in the ER. 52 We were able to validate PDIA3, a member of the family of protein disulfide isomerases (PDIs) which controls protein folding through their ability to form and break disulfide bonds, 69 as a bona fide Lhx1os interactor. Notably, we show that the downregulation of either Lhx1os or PDIA3 affects the same set of ER stress-response genes, indicating that both components impinge on the same regulatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that several Lhx1os interactors correspond to proteins associated with the ER; among them, calreticulin, calnexin, and PDIA3 are known to transiently bind newly synthesized glycoproteins in the ER. 52 We were able to validate PDIA3, a member of the family of protein disulfide isomerases (PDIs) which controls protein folding through their ability to form and break disulfide bonds, 69 as a bona fide Lhx1os interactor. Notably, we show that the downregulation of either Lhx1os or PDIA3 affects the same set of ER stress-response genes, indicating that both components impinge on the same regulatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the PDIA3 membrane complex takes part in the rapid activation of WNT5A (Wnt family member 5A) by 1,25(OH) 2 D 3 -stimulated calcium influx and generation of secondary messengers, such as cAMP and/or IP3 [ 101 ]. Finally, some reports suggested nuclear localization of PDIA3 [ 114 , 125 ]. It is well established that PDIA3 has a noncanonic ER retention signal, Q/KEDL, but the presence of a Lys-rich nuclear localization signal was also suggested [ 111 ].…”
Section: Membrane-bound Receptor(s) and Targets For Vitamin Dmentioning
confidence: 99%
“…The most studied PDI is PDIA3 (ERp57/ Grp58), which is comprised of the canonical four thioredoxin domain structure of the a-b-b-a domain organisation. In general, the a-domains of PDIs contain the catalytic CXXC active site motif, which can exhibit thiol-sulphate reductase, oxidase or isomerase activity (Darby and Creighton, 1995;Chichiarelli et al, 2022). The b-domains bind substrates with high affinity to facilitate isomerization (Klappa et al, 1998).…”
Section: Protein Disulphide Isomerasesmentioning
confidence: 99%